Design of Thumb Exoskeleton Rehabilitation Device - Rahman Mohamed Affandi, Abdul; Azam Abdullah, Shahrul; ., . (International Journal of Engineering and Technology, 2018)
Thumb nerve injury is a common injury that will affect the movement of the thumb. Exoskeleton for hand rehabilitation typically focus on finger flexion extension and do not support thumb finger opposition, a crucial function for object grasping. This paper presents the mechanical design, implementation, preliminary evaluation and proof of concept of a portable thumb exoskeleton to assist thumb opposition movements and also design of a thumb exoskeleton rehabilitation device. The thumb exoskeleton is a device to help patients during therapy and rehabilitation process. The materials of all mechanical parts n exoskeleton were 3D printed and Arduino UNO was used for movement control. The thumb exoskeleton mechanisms are combined CMC abduction-adduction and CMC flexion-extension to move the thumb using linear actuator. Linear actuator controls CMC abduction-adduction motion where when the linear actuator is fully retracts; it will conduct the CMC joint into abduction position. When the linear actuator extends, it will conduct the CMC joint into adduction positionÂ Â